Analisa Penerapan Private Cloud Computing Berbasis Proxmox Virtual Environment Sebagai Media Pembelajaran Praktikum Manajemen Jaringan - I Putu Hariyadi; Akbar Juliansyah (Universitas Bumigora, 2018)
STMIK Bumigora Mataram strives to develop a curriculum that adopts the needs of the industrial world. In the past 2 years, Network Management lecturers have experienced problems related to practicum implementation. During this time the learning process uses virtualization installed on each laboratory computer. However, the system has various weaknesses, especially related to the freedom of access and availability. The implementation of Private Cloud Computing based on Proxmox Virtual Environment (PVE) which in the cluster can be a solution to the problems faced. PVE cluster which is made using four servers and integrated with one storage server can be used as a learning media for network management practicum and support high availability so that live migration can be done. Users can manage Virtual Private Servers using Linux Container (LXC) independently with a login and limited access permission account and the configuration can be done through the console and SSH. All practicum materials were successfully tested on LXC. An FTP-based local repository built on a storage server can minimize the bandwidth usage of an Internet connection and speed up the package installation. In addition port forwarding on the gateway router can facilitate the remote access needs on LXC from the Internet.